Real-time, smartphone-based processing of lateral flow assays for early failure detection and rapid testing workflows. Issue 1 (12th December 2022) - Colombo, Monika; Bezinge, Léonard; Rocha Tapia, Andres; Shih, Chih-Jen; de Mello, Andrew J.; Richards, Daniel A.
Abstract : Herein we show that real-time analysis of lateral flow assays can be leveraged to detect test failures, decrease time-to-result, and improve testing throughput. Abstract : Despite their simplicity, lateral flow immunoassays (LFIAs) remain a crucial weapon in the diagnostic arsenal, particularly at the point-of-need. However, methods for analysing LFIAs still rely heavily on sub-optimal human readout and rudimentary end-point analysis. This negatively impacts both testing accuracy and testing times, ultimately lowering diagnostic throughput. Herein, we present an automated computational imaging method for processing and analysing multiple LFIAs in real-time and in parallel. This method relies on the automated detection of signal intensity at the test line, control line, and background, and employs statistical comparison of these values to predictively categorise tests as "positive", "negative", or "failed". We show that such a computational methodology can be transferred to a smartphone and detail how real-time analysis of LFIAs can be leveraged to decrease the time-to-result and increase testing throughput. We compare our method to naked-eye readout and demonstrate a shorter time-to-result across a range of target antigen concentrations and fewer false negatives compared to human subjects at low antigen concentrations.